The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1371/journal.pone.0006481
|View full text |Cite
|
Sign up to set email alerts
|

Colony Collapse Disorder: A Descriptive Study

Abstract: BackgroundOver the last two winters, there have been large-scale, unexplained losses of managed honey bee (Apis mellifera L.) colonies in the United States. In the absence of a known cause, this syndrome was named Colony Collapse Disorder (CCD) because the main trait was a rapid loss of adult worker bees. We initiated a descriptive epizootiological study in order to better characterize CCD and compare risk factor exposure between populations afflicted by and not afflicted by CCD.Methods and Principal FindingsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
710
5
19

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,041 publications
(784 citation statements)
references
References 63 publications
(68 reference statements)
10
710
5
19
Order By: Relevance
“…Similarly, in a recent study by Hladik et al (2014), neonicotinoids were reported frequently (40-100%) in Iowa surface water samples collected between April and July of 2013. Neonicotinoids are receiving increased scrutiny because they have been implicated in adversely affecting pollinators and linked to colony collapse disorder in bees (Spivak et al, 2011;vanEngelsdorp et al, 2009) but currently potential effects on amphibians are largely unknown.…”
Section: Water and Sediment Qualitymentioning
confidence: 99%
“…Similarly, in a recent study by Hladik et al (2014), neonicotinoids were reported frequently (40-100%) in Iowa surface water samples collected between April and July of 2013. Neonicotinoids are receiving increased scrutiny because they have been implicated in adversely affecting pollinators and linked to colony collapse disorder in bees (Spivak et al, 2011;vanEngelsdorp et al, 2009) but currently potential effects on amphibians are largely unknown.…”
Section: Water and Sediment Qualitymentioning
confidence: 99%
“…In particular, nutritionally stressed honey bees that have little protein in their bodies are less capable of enzymatically decomposing pesticides (Wahl & Ulm, 1983). The combination of nutritional stress and pesticide exposure may be additive or even synergistic and may be further compounded by stresses from parasites (Doublet, Labarussias, de Miranda, Moritz, & Paxton, 2015; vanEngelsdorp et al., 2009). Therefore, our objectives were to quantify nutritional quality and pesticide residues of pollen to gain insights into real‐world colony exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, destruction and fragmentation of natural habitats, toxicity caused by pollution and pesticides -like widely used neonicotinoids-, diseases and their spread getting easier, invasive species are leading the way (Meffe 1998;Brown & Paxton 2009;Van Engelsdorp & Meixner 2010;Blacquiere et al 2012). Honey bees also, especially wild populations that are not managed by beekeepers (including the feral populations), take their share from the situation (Oldroyd 2007;Dietemann et al 2009;Van Engelsdorp et al 2009;Genersch 2010;Evans & Schwarz 2011). …”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Ismentioning
confidence: 99%